CRISPR/Cas9 mediated mutation of mouse IL-1α nuclear localisation sequence abolishes expression. Issue 1 (December 2017) - Daniels, Michael; Adamson, Antony; Humphreys, Neil; Brough, David
Abstract Inflammation is a host defense process against infection. Inflammatory mediators include cytokines of the interleukin-1 family, such as IL-1α and IL-1β. Unlike IL-1β, IL-1α carries an N-terminal nuclear localisation sequence (NLS) and is trafficked to the nucleus. The importance of IL-1α nuclear localisation is poorly understood. Here, we used CRISPR/Cas9 to make inactivating mutations to the NLS on theIl1a gene. A colony of NLS mutant mice was successfully generated with precise knock-in mutations to incapacitate NLS function. NLS mutant mice had no gross changes in immunophenotype or inflammatory response but, surprisingly, failed to express IL-1α. We deduced that, in making specific mutations in theIl1a gene, we also mutated a long-noncoding (lnc)RNA in the complementary strand which has cis-regulatory transcriptional control of theIl1a gene itself. The mutations generated in theIl1a gene also result in mutation of the lncRNA sequence and a predicted alteration of its secondary structure, potentially explaining a subsequent failure to function as a transcriptional activator ofIl1a expression. Thus, lncRNA secondary structure may regulate IL-1α expression. Our results serve as a cautionary note that CRISPR –mediated genome editing without full knowledge of genomic context can result in unexpected, yet potentially informative observations.